Entry Deterrence Through Fixed Cost-Reducing R&D - Atallah, Gamal (Université d'Ottawa | University of Ottawa, 2006)
The paper explores the role of R&D investments reducing fixed production costs in entry deterrence. An incumbent monopolist performs R&D to reduce its fixed production costs. There is a potential entrant, which can also perform R&D for the same purpose. There are bidirectional technological spillovers between the incumbent and the potential entrant. It is shown that deterrence, which takes the form of underinvestment in R&D by the incumbent, is more likely when the spillover from the incumbent to the potential entrant is high, when the spillover from the potential entrant to the incumbent is low, and when the fixed cost is intermediate. The comparative statics of the model depend heavily on which of two cases obtains: the first case is when separation between deterrence and accommodation is dictated by the relative profitability of these strategies; the second case is when separation between these two strategies is dictated by the positivity of R&D investments. The role of two policy tools, R&D subsidies and intellectual property protection, is examined. R&D subsidies, while they generally facilitate entry, move R&D investments in socially undesirable directions, except when accommodation is the equilibrium with and without the subsidy. As for intellectual property rights, they have no effect on R&D investments (except under deterrence) and tend to reduce entry. / Le papier examine le rôle des investissements en R&D réduisant les coûts fixes de production dans la dissuasion de l’entrée. Un monopoleur établi investit dans la R&D afin de réduire ses coûts fixes de production. Un entrant potentiel peut investir en R&D pour la même fin. Il existe des externalités technologiques bidirectionnelles entre la firme établie et l’entrant potentiel. Il est démontré que la dissuasion de l’entrée, qui prend la forme d’un sous-investissement en R&D par la firme établie, est plus probable lorsque l’externalité de la firme établie vers l’entrant potentiel est élevée, lorsque l’externalité de l’entrant potentiel vers la firme établie est faible, et lorsque le coût fixe est intermédiaire. La statique comparative du modèle dépend duquel des deux cas suivants est observé: le premier cas est lorsque la séparation entre la dissuasion et l’accommodation est déterminée par la profitabilité relative de ces stratégies; le deuxième cas est lorsque la séparation entre ces deux stratégies est déterminée par la contrainte de non négativité des investissements en R&D. Le rôle de deux instruments de politique économique, les subventions à la R&D et la protection de la propriété intellectuelle, est examiné à la lumière des résultats. Les subventions, tout en facilitant l’entrée en général, affectent les investissements en R&D dans des directions socialement indésirables, sauf lorsque l’accommodation est l’équilibre avec et sans les subventions. Quant à la protection de la propriété intellectuelle, elle n’a pas d’effet sur les investissements en R&D (sauf en cas de dissuasion) et tend à réduire l’entrée.
Keywords: Entry deterrence; Fixed costs; R&D; R&D spillovers; Dissuasion de l’entrée; Coûts fixes; R&D; Externalités technologiques